Effectiveness Analysis of Anaerobic Digestion Method in Making Biogas from Animal Manure and Tofu Liquid Waste (Jurnal Ilmu dan Teknologi Hasil Ternak, 2021)
Organic waste has high COD and BOD content, so it is dangerous if disposed of directly into the environment. Organic waste processing, such as waste from livestock manure and liquid tofu waste, requires a process that can reduce COD and BOD levels as well as produce valuable products. Anaerobic digestion method is the proper process to convert complex compounds in waste into simpler compounds with methanogenic bacteria into a renewable energy product, namely biogas. On the other hand, the anaerobic digestion process can reduce COD and BOD levels in the biogas formation process. This study uses raw materials such as cow manure and chicken manure, and liquid tofu waste. The variables that produced the largest biogas were those with a ratio of 70% cow dung, 15% chicken manure, and 15% tofu liquid waste with a total of 3,251.5 mL. Then, the COD and BOD levels decreased significantly with more than 98% COD removal, and more than 95% BOD removal in all variables at the end of the anaerobic digestion process.